Perjuangan Tokoh Perempuan Etnis Tionghoa dalam Novel Pecinan: Suara Hati Wanita Tionghoa Karya Ratna Indraswari Ibrahim - Hidayah Budi Qur'ani (HISKI, 2021)
Chinese society is a part of Indonesian society. Chinese people or now familiar with Tionghoa names in Indonesia are an ethnic part that is recognized in the law. Although it has received recognition from the government, there are still many negative views about the Chinese community. Chinese ethnic women also experience injustice. The injustice experienced by ethnic Chinese women is caused by the constructs of the Chinese community which adheres to patriarchy. This study aims to describe the forms of struggle of ethnic Tinghoa women leaders to end injustice in novel Pecinan: Suara Hati Tionghoa by Ratna Indraswari Ibrahim. This study uses a liberal feminist theory that emphasizes equality between men and women. The results of this study are (1) efforts to educate women through education, (2) women must be economically independent, and (3) women's actions against adultery.